Influence of DMDBS on the morphology and mechanical properties of polypropylene cast films - Sreenivas, K.; Pol, Harshawardhan V.; Kumaraswamy, Guruswamy (Polymer Engineering and Science, 2011)
We investigate extrusion film casting (EFC) of polypropylene (PP) and examine the effects of varying the concentration of nucleating agent, dimethyl dibenzylidene sorbitol (DMDBS); melt temperature at the die exit; and the draw ratio. Addition of DMDBS increases the PP crystallization temperature, and consequently the PP lamellar repeat spacing. For the draw ratios explored, we do not observe any substantial orientation of iPP crystals for films of neat iPP. However, addition of DMDBS results in the formation of oriented PP crystals, with greater orientation for higher draw ratios. On cooling from the melt, a network of DMDBS nanofibers forms in the PP. We believe that flow-alignment of this DMDBS network templates the orientation of PP crystals. We observe that the tensile modulus and yield stress increase with PP crystal orientation. However, at high DMDBS concentrations (0.8%), films have poor mechanical strength due to formation of voids and defects. POLYM. ENG. SCI., 51:2013-2023, 2011. (C) 2011 Society of Plastics Engineers

Ice templated nanocomposites containing rod-like hematite particles: Interplay between particle anisotropy and particle-matrix interactions - Kumaraswamy, Guruswamy; Suresh, Karthika; Lama, Hisay; Basavaraj, Madivala G.; Satapathy, Dillip K. (Journal of Applied Physics, 2020)
We demonstrate that the mechanical response of ice templated nanocomposite scaffolds prepared from ellipsoidal hematite particles is determined by both the particle aspect ratio and the interaction between the particles and the matrix polymer. We ice template aqueous dispersions of hematite particles, polyethyleneimine, and diepoxy crosslinker and crosslink the polymer in the frozen state. This protocol results in the formation of elastic macroporous monoliths capable of complete recovery from large compressive strains. Hematite particles show an inversion of their surface charge with pH: they are negatively charged at a basic pH and positively charged under acidic conditions. This allows us to change the interaction between hematite particles and crosslinked matrix polymer that they are embedded in, simply by immersing the monoliths in aqueous solutions with different pH's. We report that under basic conditions, viz, when polyethyleneimine adsorbs on the particle surface, there is a decrease in the monolith modulus with an increase in the particle aspect ratio. We demonstrate that this correlates with a change in the mechanism of monolith response: from wall compression for isotropic particles to wall bending for anisotropic particles with an aspect ratio of 4. Under acidic conditions (pH=2), where hematite particles show a positive zeta potential, the monolith modulus increases with the aspect ratio of the ellipsoidal fillers. Understanding the interplay between filler aspect ratio and filler-matrix interaction has important implications for the control of nanocomposite mechanical properties.